Millimeter-wave bandpass filter on LCP using CSRR-loaded triangular-shape quarter-mode substrate integrated waveguide (2015)
A millimeter-wave two-pole bandpass filter (BPF) with an asymmetrical frequency response is realized on a flexible liquid crystal polymer substrate for wearable/conformal wireless applications. The design uses the triangular-shape quarter-mode substrate integrated waveguide (QMSIW) cavity loaded with a complementary split-ring resonator. The compact cavity shows a resonant mode below the quasi-TE1,0,0.5 mode of an original QMSIW cavity, which indicates a further size reduction. In addition, its low quality factor (Q) is useful for BPFs with broad fractional bandwidth (FBW). A surface micromachined two-pole Chebyshev BPF is realized for operation at 35 GHz with a 20 dB return loss FBW of 8% and an insertion loss of 1.7 dB. © 2015 Wiley Periodicals, Inc.